FEATURES OF LEARNING SINGING ONLINE - Івченко, Д.О.; Харченко, Ю. Т. (SWorldJournal, 2022)
Theses consider the peculiarities of learning to sing online. Methodical advice on learning vocal works by higher education students in the process of distance learning is offered. It is proved that distance learning corresponds to modern educational real